Novel mutation in SLC9A6 gene in a patient with Christianson syndrome and retinitis pigmentosum - Mignot, Cyril; Héron, Delphine; Bursztyn, Joseph; Momtchilova, Marta; Mayer, Michèle; Whalen, Sandra; Legall, Anne; Billette de Villemeur, Thierry; Burglen, Lydie (Brain & development (Tokyo. 1979), 2013)
Mutations in the SLC9A6 gene cause Christianson syndrome in boys. This X-linked syndrome is characterized by profound mental retardation with autistic behavior, microcephaly, epilepsy, ophthalmoplegia, and ataxia. Progressive cerebellar atrophy with motor regression is a remarkable feature in some patients. We report on a 22year-old male patient with Christianson syndrome carrying the novel p.Gln306X mutation. The infantile phenotype suggested pervasive developmental disorder, then profound mental retardation ensued. In later childhood, progressive cerebellar atrophy was diagnosed on serial brain MRIs and motor regression occurred. Furthermore, ophthalmological evaluations showed a retinitis pigmentosum previously unreported in this condition. We conclude that the natural history of the disease in this patient tends to confirm the degenerative nature of Christianson syndrome, and that retinal degeneration may be part of the condition. Before the onset of degeneration, the syndromic association of severe mental retardation, autistic behavior, external ophthalmoplegia, and facial dysmorphism in male patients is a clue to the diagnosis.